Does self-compassion act as a moderator for risk factors associated with PTSD symptom severity? - Cooper, Angela Marie (2011)
Threat based risk factors previously found to be associated with PTSD were investigated in a clinical population of treatment seeking individuals. Building on previous research, within evolutionary psychology, this study conceptualised experiential avoidance, shame and self-critical processes as activators of an individual’s threat based affect system, following a trauma. These processes may play a central role in the sense of ongoing current threat found in PTSD sufferers. The concept of self-compassion was also investigated; this concept has been implicated in regulating threat based processes and moderating threat based responses. This study hypothesised that individuals higher in levels of self-compassion would demonstrate lower levels of PTSD symptomatology and that levels of self-compassion would moderate the effect of each threat based risk factor on PTSD symptom severity. Correlation and hierarchical multiple regression analyses were conducted and all hypotheses were either fully or partially upheld. An interesting and unexpected moderation effect was found between self-criticism and self-compassion. It was expected that self-compassion would fully moderate the relationship between self-criticism and PTSD symptom severity, however, results show that self-compassion only moderated this relationship when the level of self-criticism was low. This suggests that the interaction between self-criticism and self-compassion is more complex than originally thought. Implications of the findings as well as ideas for future research are discussed.